2008
DOI: 10.1183/09031936.00121607
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of ozone-induced airway hyperresponsiveness and inflammation by interleukin-13

Abstract: The present study aimed to determine whether the T-helper cell type 2-derived cytokines, interleukin (IL)-4 and -13, can modulate the lung response to ozone exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 41 publications
3
28
0
Order By: Relevance
“…Interestingly, recent data from our laboratory indicated that IL-13 is involved in ozone-induced neutrophilic inflammation and AHR (30), and therefore in our ozone model, IL-13 could actually contribute to cathepsin S expression. The interactions between ozone exposure and IL-13 in the expression and activation of cathepsin S deserve further studies.…”
Section: Role Of Cathepsin S In Ozone-induced Airway Hyperresponsivenmentioning
confidence: 82%
“…Interestingly, recent data from our laboratory indicated that IL-13 is involved in ozone-induced neutrophilic inflammation and AHR (30), and therefore in our ozone model, IL-13 could actually contribute to cathepsin S expression. The interactions between ozone exposure and IL-13 in the expression and activation of cathepsin S deserve further studies.…”
Section: Role Of Cathepsin S In Ozone-induced Airway Hyperresponsivenmentioning
confidence: 82%
“…Unlike cultured cells, the whole tissue may contain mast cells, and hence the effective cytokine release may be lessened by the presence of IL-10, which would not be seen in single cell preparations. Intriguingly, despite an increase in neutrophils in rat bronchoalveolar lavage fluid, which has been shown to correlate with increased airway sensitivity (30), following poly(I:C) instillation, agonist-induced airway function in vivo was not altered compared with diluent-treated samples (25), suggesting that TLR3-activated responses in multicellular systems may be different than single cellular preparations. In other studies, the effect of poly(I:C) in human cell lines showed a modest 5-fold increase in RANTES/CCL5 in ASM (18); however, our study showed a 50-fold increase demonstrating the importance of the integrated and complicated model used in the present study.…”
Section: Discussionmentioning
confidence: 95%
“…Overall, these studies show that genes related to innate immune signaling—in particular TNF receptors 1/2 and toll-like receptors 2/4—may modulate risk related to O 3 exposure, as well as associated genes including Nfkb1 (nuclear factor of kappa light polypeptide gene enhancer in B cells 1), Jnk1 (mitogen-activated protein kinase 8; Mapk8 ), Cd44 (Cd44 antigen), Myd88 (myeloid differentiation primary response gene 88), Iai (inter-α-trypsin inhibitor), Hsp70 (heat shock protein 70), Mmp9 (matrix metallopeptidase 9), and Nos2 (nitric oxide synthase 2, inducible) (Bauer et al 2011; Cho et al 2001, 2007; Fakhrzadeh et al 2002; Garantziotis et al 2009; Hollingsworth et al 2004; Kenyon et al 2002; Kleeberger et al 2000, 2001; Williams et al 2007; Yoon et al 2007). There is also toxicologic evidence indicating that genes involved in pro- and anti-inflammatory signaling and oxidative stress modulate the O 3 response, including interleukins Il10 , Il13 , and Il6 , and Cxcr2 [chemokine (C-X-C motif) receptor 2], Marco (macrophage receptor with collagenous structure), Csb (excision repair cross-complementation group 6), and Nqo1 (Backus et al 2010; Dahl et al 2007; Johnston et al 2005a, 2005b; Kooter et al 2008; Voynow et al 2009; Williams et al 2008). Taken together, this evidence suggests the complexity of the biological mechanisms underlying airway inflammation and airway hyperresponsiveness (AHR) as well as genetic susceptibility, as previously described by Bauer and Kleeberger (2010).…”
Section: Resultsmentioning
confidence: 99%